Temporary architecture - Baker, Lisa (Berlin, [Germany] Braun Publishing, 2014)
"This volume gathers extraordinary contemporary projects from very diverse areas: from the Design Miami exhibition tent to the Expo pavilion in Shanghai; from the altar island for the pope's visit in Germany to hospital dormitories in Thailand; from the cafe for the Melbourne Food and Wine Festival to the Olympic Aquatics Center in London. Most of these concepts transgress the borderlines of architecture, art, design and social intervention, which results in a very unique form of creative freedom." -- Provided by publisher
Includes index.
Keywords: Buildings, Temporary -- Catalogs; Exhibition buildings -- Catalogs; Pavilions -- Catalogs; Architecture -- Composition, proportion, etc; Architecture, Modern -- 21st century -- Catalogs